2004
DOI: 10.3354/ame035115
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms and practical fluorescence models of the photosynthetic apparatus of red cyanobacteria and Cryptophyta designed for the fluorescence detection of red cyanobacteria and cryptophytes

Abstract: In fluorometric phytoplankton analysis, the detection of red cyanobacteria is hampered by acclimation processes of the cyanobacterial photosynthetic apparatus and spectral interferences with Cryptophyta. In order to overcome these problems, a simplified energy distribution model accounting for energy pathways in the red cyanobacterial photosynthetic apparatus and the apparatus of Cryptophyta was developed. Mathematical equations were derived that enabled calculation of the pigment content of Cryptophyta and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…The second pigment group can also include algae of other taxa, e.g., Dinophyta (Gitelson et al, 1999). It also has been reported that five spectral groups of microalgae can be identified (Beutler et al, 2002(Beutler et al, , 2004.…”
Section: Theoretical Basis Of Dcmu-fluorescence Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…The second pigment group can also include algae of other taxa, e.g., Dinophyta (Gitelson et al, 1999). It also has been reported that five spectral groups of microalgae can be identified (Beutler et al, 2002(Beutler et al, , 2004.…”
Section: Theoretical Basis Of Dcmu-fluorescence Methodsmentioning
confidence: 95%
“…It is well known that phytopigment fluorescence methods are more efficient tools for monitoring the seasonal and spatial dynamics of phytoplankton (Kolber et al, 1994;Seppala & Balode, 1998;Salonen et al, 1999;Gaevsky et al, 2002). They are widely used in photosynthesis research and in the assessment of the total phytoplankton biomass in aquatic ecosystems (Ernst, 1986;Kolber & Falkowski, 1993;Lizotte & Priscu, 1994;Lee et al, 1995;Downes & Hall, 1998;Millie et al, 2002;Beutler et al, 2002Beutler et al, , 2004. Traditionally, pulse-amplitudemodulation (PAM) fluorescence is used preferably in investigations of the ocean and deep oligotrophic lakes (Sakshaug et al, 1997;Honeywill et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The bloom development followed a typical trend already described in other Italian lakes (eg [30,31]) with a marked winter-spring peak followed by a decrease of the P. rubescens population in summer. P. rubescens cell density was around 40 10 6 cell l -1 in February and reached a maximum of about 160 10 6 cell l -1 in march [24]. The P. rubescens density then remained high throughout the month of March and at the beginning of April 2009.…”
Section: Study Areamentioning
confidence: 92%
“…In addition to phycocyanin, P. rubescens cells contain phycoerythrin the secondary pigment (phycobiliprotein) responsible for the intense red colour of its blooms [24]. Compared to phycocyanin a minor number of remote sensing studies addressed their attention to phycoerythrin.…”
Section: Introductionmentioning
confidence: 99%
“…If different spectra of light excitation are used, fluorescence emitted by algae and cyanobacteria can provide information on the taxonomic composition of phytoplankton. It has also been reported that there are five spectral groups of microalgae (Beutler et al, 2002(Beutler et al, , 2004. To visualize spectral differences in fluorescence, it is necessary to compare Cartesian coordinates of the relationships between fluorescence (F) signals excited by blue (410 nm), blue-green (510 nm), and green (540 nm) spectral regions, which are predominantly absorbed by chlorophyll and carotenoids, including fucoxanthin and phycobilins.…”
Section: Microcystis Aeruginosa Fluorescence Method Euclidean Distamentioning
confidence: 99%